MEASURING THE INFLUENCE OF E-SERVICE QUALITY TOWARD E-CUSTOMER SATISFACTION AND E-CUSTOMER LOYALTY ON ONLINE STORE BUYING BEHAVIOUR - Naurah Mahjudin; Mahjudin Mahjudin (PT. Mawadaku Sukses Solusindo, 2024)
This research is aimed to analyze the effect of e-service quality on e- customer satisfaction and e-customer loyalty. item questionnaire used as many as 20 items. Data collection is done by distributing questionnaires to customers who at least routinely shop once in a month in one or more online store in Indonesia with the number of samples of 275 respondents determined by nonprobability sampling method. Data analysis technique used is Partial Least Square-Path Modeling Reflective Multidimensional Construct (Second Order Construct) with SmartPLS 3.0 software and 5% significance level. The results obtained in this study are e-service quality has direct effect to e- customer satisfaction, e-satisfaction has a direct effect on e-customer loyalty, e- service quality has direct effect on e-customer loyalty, and e-service quality has indirect effect to e-customer loyalty through e-customer satisfaction. The advice for the company is to improve online-based services online both in terms of management and infrastructure. Suggestions for future researchers are able to refine with better theories and data and research not only on the e-commerce sector but also in other technology-based business areas.